2017
DOI: 10.1136/bmjopen-2017-016810
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of symptoms of post-traumatic stress disorder among Chinese healthcare workers exposed to physical violence: a cross-sectional study

Abstract: ObjectivesPost-traumatic stress disorder (PTSD) is a common psychological maladjustment to undergoing a traumatic event. Our aim was to measure the prevalence of PTSD among Chinese healthcare workers exposed to physical violence‚ and explore the associations of their demographic characteristics, social support, personality traits‚ and coping styles with their PTSD symptoms.MethodsA cross-sectional study was conducted using the Workplace Violence Scale, Posttraumatic Stress Disorder Checklist-Civilian Version (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 51 publications
7
58
1
7
Order By: Relevance
“…The prevalence of physical violence in this study was 4.6%, which was lower than that of previous studies in China6 27 35 36 but still higher than other countries 37. Our study also found high rates of physical violence threats and exposure to Yi Nao.…”
Section: Discussioncontrasting
confidence: 75%
“…The prevalence of physical violence in this study was 4.6%, which was lower than that of previous studies in China6 27 35 36 but still higher than other countries 37. Our study also found high rates of physical violence threats and exposure to Yi Nao.…”
Section: Discussioncontrasting
confidence: 75%
“…32 Potential healthcare-specific risk factors for PTSD include workplace violence, bullying, the death of a child, fear of exposure to infectious disease, litigation stress, use of electronic health records, long work hours, and circadian disturbance due to night shifts. 18,[27][28][33][34][35] Bellolio et al found that working primarily night shifts and working more than 80 hours per week were predictive of burnout, but found no increased risk based on specialty when these factors were controlled. 36 One surprising finding in this study was that physicians who practiced in level II trauma centers had a higher PTSD scores than physicians working in either level I centers or level III/IV centers.…”
Section: Discussionmentioning
confidence: 99%
“…The total possible score ranges from 12 to 66 points, with higher scores indicating stronger social support. The internal consistency coefficient of the total scale and subscales among Chinese samples ranged from 0.61 to 0.91, and the content and construct validities were both satisfactory [ 40 , 48 , 49 ]. In present study, the Cronbach’s α values for the whole scale and subscales were as follows: overall scale (10 items, α=0.777), objective support subscale (3 items, α=0.673), subjective support subscale (4 items, α=0.669), and support-seeking subscale (3 items, α=0.506).…”
Section: Methodsmentioning
confidence: 99%